2020
DOI: 10.22460/project.v3i2.p210-216
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Ice Breaker to Students’ Motivation in Teaching English

Abstract: This research is aimed at exploring ice breaker technique in teaching English for student at Junior High School in Cimahi. Based on the important of teaching English in Indonesia as foreign language. So by doing ice breaking before learning, it is expected that students can focus on the learning English process. In this research the writer used case study and qualitative research method. The subject of this research was on of an English teacher at One of Junior High School in Cimahi. The instrument of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…Publisher Language and Literature Faculty, University of Surakarta ISSN Print: 2621-9077 ISSN Online: 2621-9085 breaking activities might bring great gains. According to Astuti et al, (2020), an ice breaker can be employed to overcome the students' nervousness and boredom during the teaching and learning process so that they feel happier and readier to join the next core activities. Hutasoit & Tambunan (2018) point out that ice breakers are an amazing way to start a meeting, and they can be used to lessen stress and give required breaks during intense meetings.…”
Section: Vol 4 No 2 August 2021mentioning
confidence: 99%
See 3 more Smart Citations
“…Publisher Language and Literature Faculty, University of Surakarta ISSN Print: 2621-9077 ISSN Online: 2621-9085 breaking activities might bring great gains. According to Astuti et al, (2020), an ice breaker can be employed to overcome the students' nervousness and boredom during the teaching and learning process so that they feel happier and readier to join the next core activities. Hutasoit & Tambunan (2018) point out that ice breakers are an amazing way to start a meeting, and they can be used to lessen stress and give required breaks during intense meetings.…”
Section: Vol 4 No 2 August 2021mentioning
confidence: 99%
“…They provide some types of ice-breaking activities, but they are mainly concerned with offline classes. Astuti et al, (2020) also carried out a study about icebreaking, but they focus on the influence of ice-breaking activity on students' motivation of learning. Yeganehpour (2017) did a study focusing on the implementation of ice-breaking activity for productive skills.…”
Section: Vol 4 No 2 August 2021mentioning
confidence: 99%
See 2 more Smart Citations
“…Why is ice-breaker-based video an alternative and important solution for now? Because author see the results of previous studies have shown that ice breakers have a significant influence in improving motivation (Hutasoit & Tambunan, 2018) (Devi, Muncarno, & H, 2019) (Khoirullah, 2020), even ice breaker is able to improve students' learning outcomes (Solihat, Astuti, & Satriani, 2020) (Putri, 2020) (Aziz, 2019).…”
Section: Introductionmentioning
confidence: 98%